2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Seizures Following Ischemic Stroke: Frequency of Occurrence and Impact on Outcome in a Long-Term Population-Based Study

Abstract: Background & Purpose Seizures are a known complication of ischemic stroke. This study assesses the long-term incidence and characteristics of post-stroke seizures in a well-defined population. Methods Utilizing the Rochester Epidemiology Project medical record linkage system, we identified all incident cases of ischemic stroke (IS) among Rochester, MN residents from 1990-1994, and followed the patients in the comprehensive medical record through March 2014. All patients with post-stroke seizures were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
(54 reference statements)
8
65
1
Order By: Relevance
“…Other studies on small populations report varying results [Paolucci et al 1997;Bryndziar et al 2015]. Taken together, there may be room for improvement in management that should aim for seizure freedom in the same manner as in other forms of epilepsy.…”
Section: Aed Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies on small populations report varying results [Paolucci et al 1997;Bryndziar et al 2015]. Taken together, there may be room for improvement in management that should aim for seizure freedom in the same manner as in other forms of epilepsy.…”
Section: Aed Treatmentmentioning
confidence: 98%
“…In the largest study to date that was performed in the UK and followed 3310 patients with newly diagnosed stroke for an average of 3.8 years, the 10-year risk of PSE was calculated to be 12.4% [Graham et al 2013]. In a smaller, but population-wide study, 4.4% of 481 patients developed late seizures over an average follow-up period of 6.3 years [Bryndziar et al 2015]. Another study on 1020 patients reported a 2-year risk of 8.2% [Jungehulsing et al 2013].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…4 Other retrospective studies exist, but report older cases and may not reflect current clinical practice. 5,6 The findings in real-life observational studies contrast markedly with the excellent efficacy of different AEDs seen in monotherapy clinical trials. In clinical trials cited in the review, seizure freedom rates of >70% are not uncommon.…”
Section: To the Editorsmentioning
confidence: 98%
“…Moreover, ischemia-induced BBB disruption, an anatomic alteration after cerebral ischemia [1], is also a fundamental catalyst for the initiation of epilepsy [134]. A population-based study of seizure revealed that cerebral infarction was a common cause of epilepsy [135,136], and patients with a disabling cortical infarct are more likely to have epilepsy after ischemic stroke [137]. Though the mechanisms underlying epileptogenesis remain uncertain, inflammation, mitochondrial dysfunction, and oxidative stress are emerging as the major factors contributing to epileptogenesis [138].…”
Section: Epilepsymentioning
confidence: 99%